Safety of the adjuvanted recombinant zoster vaccine in adults aged 50 years or older. A phase IIIB, non-randomized, multinational, open-label study in previous ZOE-50 and ZOE-70 placebo recipients. Issue 1 (3rd January 2021) - Ocran-Appiah, Josephine; Boutry, Céline; Hervé, Caroline; Soni, Jyoti; Schuind, Anne; ,; Olsson, Åke; Anitta, Ahonen; Novo Marta, Aldea; Charles, Andrews; Mark, Arya; Eugene, Athan; et al.
Highlights: The study results were consistent with the known safety profile of RZV. A high compliance with the 2-dose vaccination schedule was achieved and no safety signal arose. The majority of AEs (pain, erythema and swelling at the injection site, and pyrexia) were associated with reactogenicity. No evidence of HZ recurrence in participants who previously had a confirmed HZ episode in the placebo arm of the ZOE studies. Abstract: Background: Efficacy of the adjuvanted recombinant zoster vaccine (RZV) against herpes zoster (HZ) was demonstrated in pivotal trials ZOE-50 (NCT01165177) and ZOE-70 (NCT01165229). This study was designed to offer RZV to placebo recipients of these parent studies. Methods: Vaccine safety and suspected HZ episode occurrence were assessed for 12 months following vaccination. Results: Of the 14, 550 eligible participants, 8687 received RZV and 97.8% completed the 2-dose schedule. During the 30-day post-vaccination period, 5175 (59.6%) participants experienced ≥ 1 unsolicited adverse event (AE), 4422 (50.9%) were vaccination-related. The most common AEs were injection-site reactions, pyrexia, and headache. During the study, 734 (8.4%) participants reported ≥ 1 serious AE (SAE) and 62 (0.7%) reported ≥ 1 potential immune-mediated disease (pIMD); 2 of each were assessed as vaccination-related. Suspected HZ episodes were reported by 30 participants (0.3%). Conclusions: Nature and incidence of AEs, SAEs, and pIMDs were as expected and in line with the parent studies.